Blending as a treatment for feeding disorders: A review of the literature. (24th September 2020) - King, Seth; Burch, Taneal
Abstract: Research indicates feeding disorders are relatively common in children. Described as combining two or more food items in a way that prevents separation, blending is recommended when the child avoids novel textures or flavors. As a nonrestrictive approach to feeding disorders, blending may appeal to consumers. The present study reviewed experimental research published from 1998 to 2018 involving the use blending to address feeding disorders. In addition to study quality, methods, and effects, this review targeted procedures used to progressively introduce novel textures. Identified studies ( n = 10) evaluated blending using single‐case designs. Studies included children ( n = 14) generally under the age of four with diagnoses of disabilities or severe feeding disorders. Although the studies provided insight into practical considerations, the research did not exhibit sufficient rigor to support the use of blending. Special considerations may nonetheless justify the use of blending in treatment. Implications for practice follow a description of findings.